Cor trıatrıatum assocıated wıth ebsteın malformatıon of atretıc mıtral valve and double outlet rıght ventrıcle - Öztunç, Funda; Akalın, Figen; Beşikçi, Resmiye (My University, 2000)
Cor triatriatum is a rare congenital cardiac anomaly and association of this pathology with Ebstein's malformation of atretic mitral valve and double outlet right ventricle has not been previously reported. We present an 11-day-old infant with this unique anomaly diagnosed by echocardiographic examination. The infant died before surgical intervention.
Keywords: Cor triatriatum, Ebstein anomaly, Mitral valve atresia, Double outlet right ventricle